Meningkatkan Kemandirian Belajar Melalui Model PBL Dengan Media Powerpoint Materi Diriku Pada SDN 28 Mengerat Sebara - Snoko Snoko; Andarweni Astuti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The background of this research is that conventional learning models are no longer effective in arousing student interest, motivation, and independence in learning. To overcome this, a progressive learning approach is needed, such as Problem Based Learning (PBL), which is supported by PowerPoint media to trigger students' interest in learning. The main objective of this research is to implement learning through the Problem Based Learning (PBL) approach using powerpoint media, with a focus on increasing student learning independence. In addition, this research also aims to increase the learning achievement targets of Catholic Religious Education in the school environment. The method used is descriptive method through classroom action research with two cycles. The results of the first cycle of research showed the results of student scores, namely that there were 2 students in the proficient category, 5 students in the proficient category, and 3 students in the feasible category. However, student independence is still not optimal, as seen from the 71% level of independent learning. In the second cycle, there was a significant increase, with 5 students in the proficient category, 4 students in the proficient category, and 1 student in the proper category. Student learning independence also experienced a high increase, reaching 90%. The implications of these findings indicate that an approach that encourages active student participation through PBL and PowerPoint media has a positive impact on increasing student independence and student learning outcomes.